2006
DOI: 10.1186/1465-9921-7-45
|View full text |Cite
|
Sign up to set email alerts
|

The role of endothelin-1 in hyperoxia-induced lung injury in mice

Abstract: These findings substantiate the involvement of the ET-1 receptors in the physiopathogenesis of hyperoxia-induced lung damage. Dual ET-1 receptor antagonism may well be of value in the prevention of hyperoxia-induced parenchymal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…The 72-hour exposure to hyperoxia in the present study resulted in increases in the basal values of both viscoelastic tissue parameters (Figure 1 ; G · BW and H · BW), which accords with the results of previous studies, where a decreased compliance was found after oxygen toxicity [ 19 , 36 38 ]. Since the hyperoxia-induced increases in G · BW and H · BW were proportional, the enhancement of ventilation heterogeneities was not likely to have played a role in these findings [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The 72-hour exposure to hyperoxia in the present study resulted in increases in the basal values of both viscoelastic tissue parameters (Figure 1 ; G · BW and H · BW), which accords with the results of previous studies, where a decreased compliance was found after oxygen toxicity [ 19 , 36 38 ]. Since the hyperoxia-induced increases in G · BW and H · BW were proportional, the enhancement of ventilation heterogeneities was not likely to have played a role in these findings [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with earlier results when immature rats were exposed to oxygen for a short time [ 16 ], the basal Raw was not affected by hyperoxia exposure (Figure 1 ) and is also in line with the notion that Raw is determined primarily by the geometry of the central conducting airways, which remained unaffected [ 19 , 34 , 35 ]. An airway obstruction was detected in earlier studies when exposure to oxygen was applied for a prolonged period (e.g.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found an early significant decrease in Edn1 lung expression following kidney IRI, and therefore found it to be an ideal candidate gene to validate our ability to accurately measure genes whose expression is deactivated following treatment. In addition, Edn-1 is a potent vasoconstrictor and its expression is associated with pulmonary endothelial injury and microvascular leak (15,21). The deactivation of gene expression at 6 h may represent a response to an increase in early protein abundance or activity, and given that it is also the gene with most links to "acute lung injury" term in the PubMed database, makes Edn1 an attractive candidate gene to be investigated as a potential mediator of AKI-induced ALI in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…endothelin‐1, ET‐1) and vasorelaxing and antiproliferative mediators (e.g. vasoactive intestinal polypeptide, VIP) may not only lead to PHT, but also alter the lung function via the bronchoactive potential of these peptides (Keith, 2000; Grimm et al 2003; Habre et al 2006; Hoeper & Rubin, 2006; McLaughlin & McGoon, 2006).…”
mentioning
confidence: 99%